PENGARUH MEDIA PEMBELAJARAN KREATIF POP-UP TERHADAP HASIL BELAJAR MENULIS TEKS PROSEDUR SISWA - Helfiyantinur Andikasari; Mayong Mayong; Usman Usman (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the effect of learning to using pop-up media on seventh grade students. Describe the effect after the use of pop-up media on seventh grade students and describe the effect of learning outcomes on writing procedure text for students. The research method used a pre-experimental design with a research design of One Group Pretest-Posttest Design. The results of this study are that there is an influence of students from 31 students before using Pop-Up media (Pretest) which is not good as many as 29 students (93.5%), while the influence of students after using Pop-Up media (posttest) is that most of them have the ability to write with the category very good as many as 24 students (77.4%). Based on the analysis of regression test, it was found that the p-value of 0.00 <0.05 which indicates a significant in learning outcomes with Pop-Up media.